Distribution of the Average Age of Marriage in Anbar Province for the Period 1997-2013-2023 - Kareem, Ahmed; Salman , Nida (Al-Adab Journal, 2025)
The province of Anbar in Iraq has experienced notable changes in the average age of marriage over the period from 1997 to 2023. Data reveals a shift in the overall mean age of marriage, reflecting changing social and cultural trends. Throughout the study period, the average age of marriage generally decreased, indicating an early onset of marital commitments. This trend may be attributed to multiple factors, including social and economic changes, cultural differences, and developments in social values. Data showcases a notable variation in the distribution of age at marriage across the years, with significant regional differences. A decrease in the average age of marriage was observed in certain areas, while it remained steady or increased in others. This suggests the influence of local factors on marriage decisions. Understanding the distribution of the average age of marriage in Anbar province is crucial for comprehending the social and cultural dynamics of the region. This data provides insight into marital trends, aids in identifying factors influencing marriage decisions, informs social policy decisions, and enhances the general understanding of social transformations in the area.